Classroom indoor air quality and noise level assessment of different educational institutions in a university area in Bangladesh - Md. Bashirul Islam; Md. Mehedi Hassan Masum; Dr. Asiful Hoque (Journal of Air Pollution and Health, 2024)
Introduction: The classroom environment is crucial for fostering effective learning and safeguarding teacher-student health. This study assessed the Indoor Air Quality (IAQ) and noise levels in classrooms across three institutions: a university, a secondary and higher secondary school (called a school and college), and a primary school. Materials and methods: Various IAQ parameters such as Particulate Matters (PM2.5 and PM10), Carbon monoxide (CO), Carbon dioxide (CO2), Total Volatile Organic Compound (TVOC), and temperature, Relative Humidity (RH), light, and noise levels were measured using calibrated instruments from February to March 2024. Results: The air pollutants and noise levels varied among the institutions. The mean values of PM2.5 (76.6 µg/m3) and PM10 (116.7 µg/m3) were highest in the primary school, while CO (0.82 ppm), light (92.9 lux), temperature (27.6 °C), and noise levels (77.6 dB) peaked in the school and college. University classrooms showed the maximum concentrations of CO2 (804.9 ppm), TVOC (32.9 ppb), and RH (58.6%). In all institutions, PM2.5, PM10, and noise levels exceeded WHO-recommended limits, whereas CO, CO2, RH, and temperature remained within their respective standards. Light levels were below Occupational Safety and Health Administration (OSHA) guidelines. Correlation analysis showed significant positive correlations between PM2.5, PM10, and CO. Hazard Quotient (HQ) values for PM2.5 and PM10 exceeded 1.0, indicating potential health risks. Variations in pollutants and noise levels among institutions may be due to classroom facilities, student density, ventilation systems, and student activities. Conclusion: Long-term exposure to IAQ pollutants and noise levels could impair cognitive function, respiratory health, and overall well-being of the students and educators. Implementing proper ventilation (e.g., HEPA filters) systems, soundproofing acoustic panels, and continuous IAQ monitoring is recommended for a safer classroom environment.